Dampak Perkembangan Teknologi Pertanian Terhadap Perubahan Sosial Masyarakat Petani - Ajib, Moh; Habiburrahman Aksa, Ahmad (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2023)
griculture is one of the characteristics of Indonesian society, especially in the province of Java. Both agriculture as an industry and to fulfill daily needs. Along with the progress of the times, many technologies have developed and always surround people's lives. Likewise, with the development of agricultural technology in Wedusan Village, many agricultural technologies have changed from traditional to modern technology. The development of agricultural technology then changes the pattern and system of agriculture and the culture of the farming community that has existed for a long time in Wedusan Village. The development of agricultural technology also has an impact on the people of Wedusan Village, the impact presented by modern agricultural technology is both positive and negative. In this study, both impacts can have implications for socioeconomics and socio-culture. All those affected by the development of technology are important structural components in the life of the farming community in Wedusan Village. The socio-cultural characteristics and character of the Wedusan Village farming community are intertwined through agriculture. Because agriculture is the meeting point of the community, both individuals and groups.